2015
DOI: 10.1016/j.jconrel.2015.05.267
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell surface induced peptide folding allows intracellular translocation of drug

Abstract: Many lead molecules identified in drug discovery campaigns are eliminated from consideration due to poor solubility and low cell permeability. These orphaned molecules could have clinical value if solubilized and delivered properly. SVS-1 is a de novo designed peptide that preferentially folds at the surface of tumor cells, adopting a β-hairpin conformation that rapidly translocates into the cytoplasm, and ultimately nucleus, of cells. SVS-1 is stable in serum and small molecules attached to the peptide are ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Results show both small molecular drugs led to potent A549 RES cell killing, with nanomolar IC 50 values. Previous results from our lab show the reverse is also true, that cells (OVCAR-3 and NCI/ADR-RES) which have gained resistance to chemotherapy are sensitive to the lytic action of SVS-1 with equal potency as drug-susceptible lines (Medina and Schneider, 2015). …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Results show both small molecular drugs led to potent A549 RES cell killing, with nanomolar IC 50 values. Previous results from our lab show the reverse is also true, that cells (OVCAR-3 and NCI/ADR-RES) which have gained resistance to chemotherapy are sensitive to the lytic action of SVS-1 with equal potency as drug-susceptible lines (Medina and Schneider, 2015). …”
Section: Resultsmentioning
confidence: 81%
“…In addition, we show that cancer cells which have gained resistance to the SVS-1 peptide retain their sensitivity towards standard chemotherapeutic agents (Figure S4). Conversely, we have also previously shown that cells resistant to small molecule chemotherapeutics can be effectively killed with oncolytic peptides (Medina and Schneider, 2015). This suggests combinatorial treatments using ACPs and anti-cancer drugs may be a potentially successful strategy in the clinic to limit resistance.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Some recent studies using CLPs, conjugating or complexing with hydrophobic anticancer drugs as drug delivery platforms, also showed selective and fast cellular uptake of drugs, which could have a similar mechanism. 26,36 This ''therapeutic drug carrier'' strategy could provide several unique benefits. The enhancement of anticancer efficacy would allow a lowered dosage of anticancer agent, reducing the side effect; the selectivity could further limit the cytotoxicity towards normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Short linear ACPs fold into amphipathic conformations upon membrane interaction Schweizer 2009), depending on hydrophobicity, amphipathicity, net charge, secondary structure, and oligomerization at the membrane level (Harris et al 2013;Hoskin and Ramamoorthy 2008). Uncovering the details of the molecular mechanisms underlying each ACP mode of action is a technically challenging but rewarding task because the information gathered from these studies can be successfully applied in the development of innovative approaches in cancer treatment (Medina and Schneider 2015). There are ACPs with high specificity and selectivity for their targets.…”
Section: Mechanisms Of Action Cellular Targets and Selectivity Of Anmentioning
confidence: 99%
“…Adapted from references Sinthuvanich et al (2012) and Gaspar et al (2015) folding is the membrane net negative charge but full membrane neutralization is not mandatory for cell death . It was recently found that SVS-1 is able to translocate across the cell membrane into the cytoplasm and into the nucleus when present in concentrations below the minimal inhibitory concentration (MIC 50 ) necessary for lytic action (Medina and Schneider 2015). The combination of SVS-1 with paclitaxel improves SVS-1 aqueous solubility and the peptide is capable of delivering and releasing paclitaxel into cancer cells and tumors in vivo without any adjuvant (Medina and Schneider 2015).…”
Section: Mechanisms Of Action Cellular Targets and Selectivity Of Anmentioning
confidence: 99%